A self-powered graphene–MoS2 hybrid phototransistor with fast response rate and high on–off ratio. (October 2015) - Li, Xiaobo; Wu, Juanxia; Mao, Nannan; Zhang, Jin; Lei, Zhibin; Liu, Zonghuai; Xu, Hua
Abstract: Here, we present a self-powered graphene–MoS2 hybrid phototransistor that simultaneously exhibits high responsivity, fast response rate and high on–off ratio. In this phototransistor, fewer-layer MoS2 serves as a sensitizer to absorb light, and high mobility graphene serves as an expressway for carrier transport, an asymmetric metal contact (titanium and palladium) design is adopted to provide a strong internal electric-field in the phototransistor channel. Under light illumination, a photovoltage arises at the two asymmetric graphene/electrode interface with photodiode mechanism, which act as a bias voltage driving the large quantity of photocarriers injected from MoS2 layer to transport in graphene channel with photoconductor mechanism. With this ingenious design, the hybrid phototransistor achieves a response rate of 0.13 ms and on–off ratio up to 1428 together with responsivity exceeding 3.0 A/W under zero bias operation. The hybrid phototransistor takes full the advantage of fast response rate of the photodiode and high responsivity of the photoconductor, which makes it has great potential for wide applications in optoelectronics, such as optical logic, optical computing and optical communication.